The Happy Hooker Based on a Book by Xaviera Hollander - Sgarro, Nicholas; Kratina, Dick; Redgrave, Lynn; Aumont, Jean-Pierre; Powell, Lovelady (MGM, 2007)
The only spark in this cheapskate version of Xaviera Hollander's much-touted life story is provided by Lynn Redgrave's believable and consistently interesting incarnation of Xaviera as a rather practical lady of no great imagination but a deal of energy. The script and direction are both doggedly routine. Anything like a sex scene is promptly elided out of existence, a promising line of social satire fails to develop, and the sorry light cast on the male characters, all roundly and condescendingly patronised by the women, is allowed to develop swiftly into overripe farce. A distinct aura of missed opportunity hangs about the proceedings, which make quite a good job of sidestepping the relevant issues. [www.timeout.com]
Keywords: DVD-Video